2015
DOI: 10.1590/s1806-37132015000100009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and nasal polyposis in cystic fibrosis: update on diagnosis and treatment

Abstract: Although cystic fibrosis (CF) is an irreversible genetic disease, advances in treatment have increased the life expectancy of CF patients. Upper airway involvement, which is mainly due to pathological changes in the paranasal sinuses, is prevalent in CF patients, although many are only mildly symptomatic (with few symptoms). The objective of this literature review was to discuss the pathophysiology and current therapeutic management of chronic rhinosinusitis (CRS) in CF patients. The review was based on curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 58 publications
1
62
0
7
Order By: Relevance
“…In the present study, the most common complaint in children was nasal congestion (61.7%). In addition, there was no relationship between symptoms and age, sex, height, and weight that was consistent with the most recent studies (9,17,18). In our study, 31.9% of nasal polyps were diagnosed using rigid endoscope examination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the most common complaint in children was nasal congestion (61.7%). In addition, there was no relationship between symptoms and age, sex, height, and weight that was consistent with the most recent studies (9,17,18). In our study, 31.9% of nasal polyps were diagnosed using rigid endoscope examination.…”
Section: Discussionsupporting
confidence: 93%
“…Many patients do not report Sino nasal symptoms. Involvement of the upper respiratory tract occurs as chronic rhino sinusitis and nasal polyps that can affect the quality of life in these patients (6)(7)(8)(9). Nasal polyps are the most common finding on physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this is related to these patients lack of a “normal” baseline for comparison. Others have proposed that sinonasal symptoms are reported to be low because they are overshadowed by other systemic symptoms, such as significant pulmonary and/or gastrointestinal symptoms . Regardless of the exact reasoning as to why CF patients do not report a high level of sinonasal morbidity, the low symptom burden in these patients makes the assessment of response to treatment difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In the 6 studies included in our review, the delivery of dornase was via different inhalational devices and the impact this may have had on outcomes and the comparison of those outcomes is unknown. The PARI‐SINUS™ device delivers vibrating aerosol particles with pressure gradients in nasal and paranasal cavities, allowing for aerosol diffusion into passively ventilated areas . The standard nasal device does not sufficiently deliver drugs to the nasal cavity and goes mainly to the posterior nasopharynx.…”
Section: Discussionmentioning
confidence: 99%